Treuhand transdisziplinär: Deformation, Disruption, Dynamik, Devaluation; Treuhand transdisciplinary: Deformation, disruption, dynamics, devaluation - Marcus Böick (Wirtschaftsdienst, 2021)
Die Geschichte des wirtschaftlichen Wiederaufbaus im post-sozialistischen Ostdeutschland nach 1990 ist vor allem mit der viel diskutierten Treuhandanstalt verbunden. Verschiedene Narrative beleuchten langfristige strukturelle Veränderungen, kurzfristige Brüche, mittelfristige Dynamiken sowie die Rahmung kultureller Reflexionen auf individueller oder kollektiver Ebene. Diese Muster könnten nicht nur helfen, heuristische Brücken zwischen verschiedenen Disziplinen wie Sozialwissenschaften, Ökonomie oder Geschichte in diesem neu aufkommenden Wissenschaftsbereich zu bauen, sondern auch dazu beitragen, diese Forschung in breitere Themen auf europäischer oder sogar globaler Ebene einzubetten. – – This paper examines new options regarding interdisciplinary perspectives on the history of economic reconstructions in post socialist Eastern Germany after 1990, mostly connected to the muchdebated Treuhandanstalt (Trusteeship Agency). By discussing different narratives, a brief, abstract framework is presented by highlighting longterm structural changes, shortterm disruptions, midterm dynamics as well as framing cultural reflections on an individual or collective level. These patterns could help to build heuristic bridges between different disciplines (like social sciences, economics, or history) in this re-emerging scientific area and to embed this research in broader themes on a European or even global scale.
Keywords: N94; O4; P2; R1; 330